2019
DOI: 10.1007/s40262-019-00755-3
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic and Pharmacodynamic Analysis of GLPG1690, an Autotaxin Inhibitor, in Healthy Volunteers and Patients with Idiopathic Pulmonary Fibrosis

Abstract: Background and Objectives GLPG1690 is an autotaxin inhibitor in development for the treatment of idiopathic pulmonary fibrosis. Several publications suggested a role of autotaxin in the control of disease-affected lung function and of lysophosphatidic acid in lung remodeling processes. The aim of the current article was to describe the exposure–response relationship of GLPG1690 and further develop a rational basis to support dose selection for clinical trials in patients with idiopathic pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 17 publications
4
26
0
Order By: Relevance
“…Modeling was performed to determine relationships between treatment exposure and response (eMethods in Supplement 3). 18…”
Section: Pharmacokinetic and Pharmacodynamic Assessmentsmentioning
confidence: 99%
“…Modeling was performed to determine relationships between treatment exposure and response (eMethods in Supplement 3). 18…”
Section: Pharmacokinetic and Pharmacodynamic Assessmentsmentioning
confidence: 99%
“…LPA mediates inflammation and fibrosis (8,11) and has been linked to the pathogenesis of SSc (12,13). In human plasma, LPA C18:2 is the most common species, containing a fatty acid side chain of 18 carbon atoms, including 2 unsaturated bonds (14,15). In vitro and clinical studies have demonstrated that targeting the autotaxin/LPA pathway could modulate skin pathology in SSc (10,12,16,17).…”
Section: Introductionmentioning
confidence: 99%
“…15 Increased ATX and LPA levels have also been found in the lung tissues and bronchoalveolar lavage lung fluid, respectively, of patients with IPF. 12,16 Ziritaxestat is a novel ATX inhibitor 17 that was in development as a treatment for IPF and systemic sclerosis. 18 Phase 2 studies have been completed in patients with IPF 19 and systemic sclerosis 20 ; however, phase 3 trials of ziritaxestat in addition to standard-ofcare treatment in patients with IPF were halted because the benefit-risk profile of ziritaxestat was found to no longer support continuation of these trials.…”
mentioning
confidence: 99%